Team incentives and performance: Evidence from a retail chain - Guido Friebel; Matthias Heinz; Miriam Krueger; Nikolay Zubanov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In a field experiment with a retail chain (1,300 employees, 193 shops), randomly selected sales teams received a bonus. The bonus increases both sales and number of customers dealt with by 3%. Each dollar spent on the bonus generates 3.80 in sales, and 2.10 in profit. Wages increase by 2.2% while inequality rises only moderately. The analysis suggests effort complementarities to be important, and the effectiveness of peer pressure in overcoming free-riding to be limited. After rolling out the bonus, treatment and control shops' performance converge, suggesting long-term stability of the treatment effect.
Keywords: J3; L2; M5; 330; management practices; randomized controlled trial (RCT); field experiment; insider econometrics; wage inequality